New Corporate Governance in the Post-Crisis World - Hilb, Martin (World Bank, Washington, DC, 2012)
The new corporate governance concept is articulating goes back to the roots of good corporate governance, which is the ability to act as a visionary and effective decision body, exerting both strategic leadership and control. It's also an invitation to think twice about the applicability of "best practices" in different legal contexts and business models. Arguably, despite some common features, the appropriate corporate governance of a family business company will differ from that of a large listed company. In addition, both the financial crisis and previous cases of large corporate failures have raised critical questions about the role of board directors in risk management. Are boards sufficiently equipped with the necessary knowledge, skills and expertise to provide the appropriate strategic vision and control function? The answer is certainly more complex and nuanced than it seems. Overly generalist boards may not grasp certain technicalities (with dreadful consequences), yet overly technical boards may completely miss the big picture.